2008
DOI: 10.1159/000113307
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Malaria: Role of Nutritional Interventions

Abstract: Malaria is a leading cause of morbidity and mortality among children, particularly in sub-Saharan Africa. Although substantial progress has been made in the treatment of pediatric malaria with artemisinin-based combination therapy, there remain many obstacles to the effective implementation of these highly efficacious new treatment options. Similarly, while effective tools are available for the prevention of malaria in children, scaling these up so that they have a clear impact on malaria-associated morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 226 publications
0
4
0
Order By: Relevance
“…There are a limited number of clinical trials that have evaluated the potential effects of micronutrient supplements on children living in malaria-endemic areas which lead to different outcomes either protective, adverse, or no effects [ 31 , 41 ]. In this study, CSB and LNS interventions have not decreased the prevalence of asymptomatic malaria compared to the control group which did not support the study hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of clinical trials that have evaluated the potential effects of micronutrient supplements on children living in malaria-endemic areas which lead to different outcomes either protective, adverse, or no effects [ 31 , 41 ]. In this study, CSB and LNS interventions have not decreased the prevalence of asymptomatic malaria compared to the control group which did not support the study hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Weight-for-age is used to assess underweight as an indicator of under nutrition because of its availability and its ability to capture both stunting (generally associated with long term under nutrition) and its wasting (manifestation of recent and acute under nutrition) [25]. There is substantial evidence that malaria contribute to impaired weight and height gain in children but the impact of under nutrition on malaria is complex [19]. The prevalence of underweight in the community (7.0%) and hospital (6.9%) among malaria uninfected sampled population was low, and the infected boys had the highest prevalence.…”
Section: Communities Hospitalsmentioning
confidence: 99%
“…High level of poverty which has a define effect on nutritional status has been linked to the endemicity of malaria in the Sub-Saharan Africa [7]. Several studies have shown associations between malaria and protein energy malnutrition, poor growth and certain micronutrient deficiencies among children [8]. Malnutrition has a negative effect on the body's defence mechanism; the lack of certain essential nutrients which help the body to boost its immune system can make it susceptible to malaria infection.…”
Section: Introductionmentioning
confidence: 99%